The organisation of the English secular church in the reign of Henry I - Brett, M; Brett, Martin (1969)
﻿ Summary. This is a study of the structure within which the English church was governed and administered under Henry I, although it has sometimes been necessary to draw on evidence for a rather longer period. Although the Anglo-Norman church was recruited from a single bodey of men governed by a single powerful king there was still an importand sense of separate identity in the English church, particularly expressed in the celebration of 'national' councils. By 1135 it was also very rare for the Normans appointed to high office in the English churchto have spent any substantial period in a Norman benefice; the English church was at least as distinct from its Norman counterpart as English society. By the end of the reign it was easier to define the limits of this church; although York retained important claims north of the Scottish border the creation of the diocese of Carlisle has done much to make the ecclesiastical frontier coincide with political realities; in Ireland the primatial claims of canterbury had recieved a decisive check, but the absorption of the Welsh hierarchy into her province was almost complete, at least at the higher levels. [continued in text ...]